Synthesis and antifungal activity of 1,2,3-triazole containing fluconazole analogues - Aher, Nilkanth G.; Pore, Vandana S.; Mishra, Nripendra N.; Kumar, Awanit; Shukla, Praveen K.; Sharma, Aanchal; Bhat, Manoj K. (Bioorganic & Medicinal Chemistry Letters, 2009)
Fluconazole based novel mimics containing 1,2,3-triazole were designed and synthesized as antifungal agents. Their antifungal activities were evaluated in vitro by measuring the minimal inhibitory concentrations (MICs). Compounds 12, 15, and 16 were found to be more potent against Candida fungal pathogens than control drugs fluconazole and amphotericin B. The studies presented here provide structural modi. cation of fluconazole to give 1,2,3-trazole containing molecules. Furthermore, these molecules were evaluated in vivo against Candida albicans intravenous challenge in Swiss mice and antiproliferative activities were tested against human hepatocellular carcinoma Hep3B and human epithelial carcinoma A431. It was found that compound 12 resulted in 97.4% reduction in fungal load in mice and did not show any profound proliferative effect at lower dose (0.001 mg/ml). (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; Antifungal agent; bile acid; Conjugates; Fluconazole

Cytotoxic activity of 9,10-dihydro-2,5-dimethoxyphenanthrene-1,7-diol from Eulophia nuda against human cancer cells - Shriram, Varsha; Kumar, Vinay; Kishor, P. B. Kavi; Suryawanshi, Sharad B.; Upadhyay, Ankur K.; Bhat, Manoj K. (Journal of Ethnopharmacology, 2010)
Ethnopharmacological relevance: Eulophia nuda L. (Orchidaceae) is a medicinally important terrestrial orchid used for the treatment of tumours and various health problems by the local healers throughout the Western Ghats region in Maharashtra (India). Aim of the study: To isolate the active molecule from Eulophia nuda and to study its cytotoxic potential against human cancer cells. Materials and methods: The crude methanolic extract of Eulophia nuda tubers was fractionated by stepwise gradient of the solvents chloroform-methanol to isolate the pure compound. Isolated pure compound was assessed for its cytotoxic potential against human breast cancer cell lines, MCF-7 and MDA-MB-231 using MTT assay. Structure elucidation of the isolated active compound was carried out by extensive spectroscopic analysis including (1)H NMR, (13)C NMR, NOESY, COSY, LC-MS and IR. Results: The isolated active molecule was identified as phenanthrene derivative 9,10-dihydro-2,5-dimethoxyphenanthrene-1,7-diol. This compound showed good antiproliferative activity against human breast cancer cell lines MCF-7 (91%) and MDA-MB-231 (85%) at 1000 mu g/ml concentration. Conclusion: 9,10-Dihydro-2,5-dimethoxyphenanthrene-1,7-diol from Eulophia nuda tubers showed good growth suppressive effect against human cancer cell lines MCF-7 and MDA-MB-231 making it a potential biomolecule against human cancer. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Cytotoxic activity; Eulophia nuda; Phenanthrene derivatives